Anticancer potency of novel organometallic Ir(iii) complexes with phosphine derivatives of fluoroquinolones encapsulated in polymeric micelles. Issue 18 (6th August 2020) - Kozieł, Sandra; Komarnicka, Urszula K.; Ziółkowska, Aleksandra; Skórska-Stania, Agnieszka; Pucelik, Barbara; Płotek, Michał; Sebastian, Victor; Bieńko, Alina; Stochel, Grażyna; Kyzioł, Agnieszka
Abstract : A 3D model of cell culturing (spheroids) was explored and the anticancer potential of the selected novel organometallic Ir(iii ) complex encapsulated in Pluronic p-123 micelles was clearly proved. Abstract : Novel half-sandwich iridium(iii ) complexes with aminomethyl(diphenyl)phosphine derived from fluoroloquinolones (IrPCp, IrPSf, IrPLm, IrPNr ) were studied as possible anticancer chemotherapeutics and showed higher potency than other well-known metal-based agents i.e., Pt(ii ) drugs. All compounds were characterized by elemental analysis, selected spectroscopic methods ( i.e., absorption and fluorescence spectroscopy, NMR), ESI-MS spectrometry, X-ray diffraction, and electrochemical techniques. The studied complexes exhibited promising cytotoxicity in vitro with IC50 values significantly lower than that of the reference drug – cisplatin. The insight into the mode of action revealed the uniform distribution of the Ir(iii ) complexes in both the nucleus and cytoplasm (Pearson's co-localization coefficient of 0.63). Precise cytometric analysis provided clear evidence for the predominance of apoptosis in the induced cell death. The activation of caspase-3/7 along with the decrease of mitochondrial membrane potential also confirmed the apoptotic cell death. The investigated Ir(iii ) complexes may induce changes in the cell cycle leading to G2/M phase arrest. ROS generation as a plausible pathway responsible for the cytotoxicity was confirmed by determination of redox potentials enabling efficient ROS production. Furthermore, Pluronic P-123 micelles loaded with selected Ir(iii ) complexes were proposed to overcome low solubility and to minimize serious systemic side effects by administering the complex in a controlled manner. The resulting nanoformulations (IrPCp_M, IrPNr_M ) facilitated efficient drug accumulation for human lung adenocarcinoma and human prostate carcinoma (A549 and DU-145 cell lines), as demonstrated by confocal microscopy and ICP-MS analysis. In vitro cytotoxicity assays were also carried out within multicellular tumor spheroids and efficient anticancer action on these 3D assemblies was demonstrated.